Business Feasibility Study Analysis on Coffee Shop Business : Case Study on Meine Welt Coffee in Palangka Raya - Ahmad Hidayat; Tonich Uda; Windy Utami Putri; Rinto Alexandro (Edunomics Journal, 2022)
In recent years, SMEs engaged in the creative industry sector in the coffee shop business have continued to show their existence, one of which is the Meine Welt Coffee coffee shop business. This study aims to analyze the feasibility of a coffee shop business at a Meine Welt coffee shop business to find out whether the current business can provide the expected financial benefits with a qualitative approach, namely a research procedure that produces descriptive data collected through interviews, observations and documentation. Sources of data used are primary and secondary data. While the analysis technique used is qualitative analysis techniques to assess legal aspects, environmental aspects, market and marketing aspects, technical and technological aspects, management and human resources aspects and financial aspects. The results of this study indicate that based on non-financial aspects this coffee shop is feasible to run. Analysis of the financial aspects of the Meine Welt coffee shop shows the NPV value of IDR 115,505,164, the Payback Period (PP) for 3 years and 3 months, Profitability Index (PI) 1.78, Internal Rate of Return (IRR) of 36.60%, and Average Rate of Return (ARR) of 160%.